2011
DOI: 10.1128/aac.01215-10
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Analysis of Salmonella enterica Serovar Typhimurium T000240 Reveals the Acquisition of a Genomic Island Involved in Multidrug Resistance via IS 1 Derivatives on the Chromosome

Abstract: Salmonella enterica serovar Typhimurium is frequently associated with life-threatening systemic infections, and the recent global emergence of multidrug resistance in S. enterica isolates from agricultural and clinical settings has raised concerns. In this study, we determined the whole-genome sequence of fluoroquinoloneresistant S. enterica serovar Typhimurium T000240 strain (DT12) isolated from human gastroenteritis in 2000. Comparative genome analysis revealed that T000240 displays high sequence similarity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 44 publications
1
40
0
Order By: Relevance
“…A unique 82-kb genomic island, GI-DT12, was recently reported in an S. Typhi-murium isolate collected from a human gastroenteritis case. The region was believed to have been acquired by horizontal gene transfer and harbored a class one integron, a mer operon, and several resistance genes believed to contribute to survival ability in adverse environments (39). This raises the issue of whether the acquisition of the chromosomal translocated region of the Zambian S. Typhi isolates was the consequence of an adverse environment due to poor sanitation.…”
Section: Discussionmentioning
confidence: 99%
“…A unique 82-kb genomic island, GI-DT12, was recently reported in an S. Typhi-murium isolate collected from a human gastroenteritis case. The region was believed to have been acquired by horizontal gene transfer and harbored a class one integron, a mer operon, and several resistance genes believed to contribute to survival ability in adverse environments (39). This raises the issue of whether the acquisition of the chromosomal translocated region of the Zambian S. Typhi isolates was the consequence of an adverse environment due to poor sanitation.…”
Section: Discussionmentioning
confidence: 99%
“…The complete or partial loss of core genes was noted primarily in invasive strain D23580, MDR strain T000240, and in two closely related strains, UK-1 (called the "universal killer" for its pronounced invasion and virulence properties) and 14028S (15,17,39,40). This finding highlights a possible central role for gene inactivation in the evolution of fitness diversity in Salmonella Typhimurium strains.…”
Section: Discussionmentioning
confidence: 73%
“…Previous work demonstrated that this island has most likely helped the isolate to adapt to adverse environmental conditions such as extremely polluted sewage (17). In the additional 12 genomes, only two more genomic islands (in strains DT104, 138736, and L-3553) were identified that also carried both MDR and fitness genes.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations